Heart-Microcirculation Connection: Effects of ANP (Atrial Natriuretic Peptide) on Pericytes Participate in the Acute and Chronic Regulation of Arterial Blood Pressure. Issue 5 (November 2020) - Špiranec Spes, Katarina; Chen, Wen; Krebes, Lisa; Völker, Katharina; Abeßer, Marco; Eder Negrin, Petra; Cellini, Antonella; Nickel, Alexander; Nikolaev, Viacheslav O.; Hofmann, Franz; Schuh, Kai; Schweda, Frank; et al.
Abstract : Cardiac ANP (atrial natriuretic peptide) moderates arterial blood pressure. The mechanisms mediating its hypotensive effects are complex and involve inhibition of the renin-angiotensin-aldosterone system, increased natriuresis, endothelial permeability, and vasodilatation. The contribution of the direct vasodilating effects of ANP to blood pressure homeostasis is controversial because variable levels of the ANP receptor, GC-A (guanylyl cyclase-A), are expressed among vascular beds. Here, we show that ANP stimulates GC-A/cyclic GMP signaling in cultured microvascular pericytes and thereby the phosphorylation of the regulatory subunit of myosin phosphatase 1 by cGMP-dependent protein kinase I. Moreover, ANP prevents the calcium and contractile responses of pericytes to endothelin-1 as well as microvascular constrictions. In mice with conditional inactivation (knock-out) of GC-A in microcirculatory pericytes, such vasodilating effects of ANP on precapillary arterioles and capillaries were fully abolished. Concordantly, these mice have increased blood pressure despite preserved renal excretory function. Furthermore, acute intravascular volume expansion, which caused release of cardiac ANP, did not affect blood pressure of control mice but provoked hypertensive reactions in pericyte GC-A knock-out littermates. We conclude that GC-A/cGMP–dependent modulation of pericytes and microcirculatory tone contributes to the acute and chronic moderation of arterial blood pressure by ANP. Graphic Abstract: A graphic abstract is available for this article. Abstract : Supplemental Digital Content is available in the text.